Adapting to the disappearing perimeter. Issue 8 (August 2017) - Mansfield-Devine, Steve
Abstract : Security professionals have been warning for years that the traditional network perimeter is vanishing, along with the protections provided by security solutions that once lived there. In this interview, Kirsten Bay, CEO of Cyber adAPT, explains how new technologies such as the Internet of Things (IoT) are forcing us to think more deeply about the kinds of defences we use – and what we're trying to defend.